Design of a Website-Based Company Profile at SMK Al-Idrus Kutai Kartanegara - Mu Fahrozi; Aspianur; Wawan Pranoto (Penerbit Jurnal Indonesia, 2024)
The development of technology in education encourages SMK Al-Idrus Kutai Kartanegara to embrace the digital world. This study aims to address the challenges of limited resources in integrating web design skills by developing a web-based company profile application using the prototyping method. The program involves stages such as requirement gathering, prototype development, user evaluation, and final product development. The resulting application includes interfaces such as a homepage, admin panel, news section, departments, student admission (PPDB), school profile, and login page. Through this activity, students gain practical experience in web development, enabling them to compete in the digital era and meet the demands of the information technology and graphic design industries.